2021
DOI: 10.2217/3dp-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D-Printer Settings for Producing Personal Protective Equipment

Abstract: Aim: COVID-19 resulted in a shortage of personal protective equipment. Community members united to 3D-print face shield headbands to support local healthcare workers. This study examined factors altering print time and strength. Materials & methods: Combinations of infill density (50%, 100%), shell thickness (0.8, 1.2 mm), line width (0.2 mm, 0.4 mm), and layer height (0.1 mm, 0.2 mm) were evaluated through tensile testing, finite element analysis, and printing time. Results: Strength increased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The prototype was developed in a few stages. Initially, the team reviewed the existing face shields and found that the technology was absent which needs to be incorporated [18,19]. Thereafter, technological ideas were generated and an idea to integrate an infrared sensor within the face shield was finalized.…”
Section: Development Processmentioning
confidence: 99%
“…The prototype was developed in a few stages. Initially, the team reviewed the existing face shields and found that the technology was absent which needs to be incorporated [18,19]. Thereafter, technological ideas were generated and an idea to integrate an infrared sensor within the face shield was finalized.…”
Section: Development Processmentioning
confidence: 99%